(untitled) (Journal of the College of Basic Education, 2022)
The Princess Amena Abraheem Is One Of The Most Great Characters in the Twentieth Century , She is the only women called " Basha " during Ottoman era . her central leanings are taking care of poor and patients people and support of Charitable Organizations